African Primary Care Research: Performing a programme evaluation - Lilian Dudley (AOSIS, 2014)
This article is part of a series on Primary Care Research in the African context and focuses on programme evaluation. Different types of programme evaluation are outlined: developmental, process, outcome and impact. Eight steps to follow in designing your programme evaluation are then described in some detail: engage stakeholders; establish what is known; describe the programme; define the evaluation and select a study design; define the indicators; planand manage data collection and analysis; make judgements and recommendations; and disseminate the findings. Other articles in the series cover related topics such as writing your research proposal, performing a literature review, conducting surveys with questionnaires, qualitative interviewing and approaches to quantitative and qualitative data analysis.